Including Containers with Dangerous Goods in the Cargo Mix Problem for Container Vessel Stowage - Kiros Gebrearegawi Kebedow; Johan Oppen (Communications - Scientific letters of the University of Zilina, 2019)
The Cargo Mix Problem (CMP) chooses and distributes types of containers to load into bay subsections of a container vessel. In this paper, we extend existing Mixed Integer Programming models for the CMP by considering containers with dangerous goods. We show that our model can be optimally solved in reasonable time using standard software.